Fermentation Products, Microbial Protein Synthesis, and Hydrolytic Enzymes Activity of Rumen Fluids Local Beef Cattle Supplemented by Direct-Fed Microbials and Waru Leaf Flour - Nursetiyadi, Dhany; Bata, Muhammad; Rahayu, Sri (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
The aim of this study was to evaluate the effect of Waru Leaf Flour (WLF) and Direct-Fed Microbials (DFM) supplementation on volatile fatty acid (VFA) and ammonia (N-NH3) concentrations, total protozoa, microbial protein synthesis (MPS), and the specific activity of cellulase, amylase, protease in rumen fluids of local beef cattle. The study was conducted as an experimental investigation using a factorial Completely Randomized Design (FCRD). The first factor were three levels of DFM (P) mixed with rice straw (0%, 0.5%, and 1% dry matter of rice straw). The second factor consisted of three levels of WLF supplementation (D) in concentrates (0%, 0.24%, and 0.48% of dry matter concentrate). This resulted nine treatment groups, each it replicated three times.The diet composition consisted of rice straw and concentrate at 40:60 ratio (% dry matter). The interaction between DFM and WLF had a statistically significant impact (p<0.01) on the rumen fluid's total protozoa, N-NH3, and protein content. However, this interaction was not statistically significant (P>0.05) in relation to VFA, MPS, cellulase, amylase, and protease activity. While no significant interaction were observed for total VFA, cellulase, amylase, and protease, DFM supplementation had a statistically significant effect (P<0.01) on reducing enzymes activity, and total VFA (P<0.05). SDS-PAGE and zymography analyzes showed two protease molecules at all treatments with molecular weight of 144 kDa and 133 kDa, cellulase molecules at 62-67 kDa and 19-21 kDa respectively. The addition of DFM showed a new protease band, they had a measurement of 14 and 25 kDa.This study provides valuable insights into enzyme activities in rumen, particularly protease, cellulase, and amylase. The results suggest that the combination of 0.24% WLF and 0.5% DFM supplementation holds promise for optimizing rumen conditions and improving the performance of local beef cattle.